É ensinando que se aprende: um estudo sobre o ensino de projeto no Curso de Arquitetura e Urbanismo da Universidade Federal do Rio Grande do Norte (CAU UFRN) - Rodriguez, Virginia Laise da Silva (2008)
You cannot teach architectonic design, but only learn it. This sentence was, during some decades, especially during the modernism, the starting point, adopted by several architectonic design professors, when they had to approach their subject. An attitude that, some years ago, was reviewed and fighted by area s experts. This paper join this criticism, and try to add something to the pre-existing discussion, analyzing with the case-study method all the subjects related with architectonic design of the Architecture and Urbanism degree, at Universidade Federal do Rio Grande do Norte CAU/UFRN . The aim is to identify and analyze the teaching methodologies used by the professors and their effects related to the students. To reach this purpose four different methods were used: i) Professors interviews; ii) Different forms submitted to students and professors; iii) Daily practice s observation, developed during classes; iv) Documents analysis about the degree (historical development and subjects) and about the subjects themselves (summaries, table of contents and planning). Studying the results, it was possible to underline that, in spite of the efforts of some of the professors to find a way to teach with more appropriate educational and pedagogic bases, some of the teaching methodologies, criticized in articles dealing with the matter, were still used. With regard to these, the research pointed out some suggestions that could help to improve the teaching and learning process, joining professors and students that are the most important subjects of the teaching activity. Developing the idea living in the paper s title Teaching and learning , it s now clear that only the practice, through the improvement of the pedagogic techniques, together with critical analysis can help the professors to reach a relationship level, regarding the teaching and learning process, as that described in the epigraph s text, into which teaching and learning, can t be done only by one of the process subject, but must be lived by both of them: professors and students